Evidence-Based Guideline for Neuropathic Pain Interventional Treatments: Spinal Cord Stimulation, Intravenous Infusions, Epidural Injections and Nerve Blocks - Angela Mailis; Paul Taenzer (Pain Research and Management)
BACKGROUND: The Special Interest Group of the Canadian Pain Society has produced consensus-based guidelines for the pharmacological management of neuropathic pain. The society aimed to generate an additional guideline for other forms of neuropathic pain treatments.